Pengaruh Rebranding dan Brand Image Terhadap Penjualan Produk Tos Tos - Novia, Wahyuni Zul Dwi; Sulaiman, Fahmi; Sulaiman, Jihan (TIN: Terapan Informatika Nusantara, 2024)
This research was conducted at PT. Saripati Prima Niaga, this study aims to determine the effect of rebranding and brand image on sales of tos tos products, this study uses quantitative research methods, and sampling uses the slovin formula with 86 respondents. Based on the results of this study, it produces a very high correlation value (r = 0.937 and r = 0.954). The determination coefficient of 91.8% indicates that the rebranding and brand image variables together significantly affect sales. The results of the T test and F test strengthen this finding by showing that both variables simultaneously and partially have a significant effect on increasing sales, according to the regression equation Y = 0.480 + 0.329 (X1) + 0.653 (X2) simultaneously producing that the rebranding and brand image variables have a significant effect on sales, rebranding and brand image affect 91.8% while the remaining 8.2% are influenced by other factors not studied.